How to Start and Build Microsurgery Practice—Topics on Success and Sustainability: Global/International - Jin Geun Kwon, MD; Hyunsuk Peter Suh, MD, PhD; Changsik John Pak, MD, PhD; Joon Pio Hong, MD, PhD, MMM (Plastic and Reconstructive Surgery, Global Open, 2024)
Summary:. Many young microsurgeons begin their careers at established hospitals where microsurgery resources are limited. This article shares the authors’ experiences in overcoming challenges and establishing a microsurgery practice in a new hospital. Due to the lack of equipment, limited support from colleagues, absence of discussion partners, fear of failure, and unpredictable situations, many aspiring microsurgeons lose their motivation. The purpose of this article is to guide future microsurgeons by describing the author’s actions and suggesting improvements for their first free flap case. Key factors for building a successful, sustainable, and enjoyable microsurgery practice include remembering your training and mentors, acquiring fundamental knowledge of microsurgery, creating a supportive ecosystem, and having fun.